2017
DOI: 10.1002/adma.201606671
|View full text |Cite
|
Sign up to set email alerts
|

Smectic Layer Origami via Preprogrammed Photoalignment

Abstract: Hierarchical architecture is of vital importance in soft materials. Focal conic domains (FCDs) of smectic liquid crystals, characterized by an ordered lamellar structure, attract intensive attention. Simultaneously tailoring the geometry and clustering characteristics of FCDs remains a challenge. Here, the 3D smectic layer origami via a 2D preprogrammed photoalignment film is accomplished. Full control of hierarchical superstructures is demonstrated, including the domain size, shape, and orientation, and the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 53 publications
0
41
0
Order By: Relevance
“…Ok et al [44] reported the multi-rubbing induced spatial arrangement of TFCDs, which was enabled by a tendency to maintain organization in the N phase once transitioned to the SmA phase. Sharing the function of guiding molecular orientation with the rubbing method, a photo-alignment technique has become popular [45][46][47][48][49]. It can overcome the drawbacks of the rubbing, including the mechanical damage and electrostatic charges.…”
Section: Rubbingmentioning
confidence: 99%
“…Ok et al [44] reported the multi-rubbing induced spatial arrangement of TFCDs, which was enabled by a tendency to maintain organization in the N phase once transitioned to the SmA phase. Sharing the function of guiding molecular orientation with the rubbing method, a photo-alignment technique has become popular [45][46][47][48][49]. It can overcome the drawbacks of the rubbing, including the mechanical damage and electrostatic charges.…”
Section: Rubbingmentioning
confidence: 99%
“…Copyright 2016, American Chemical Society. (C) Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Light‐activated Liquid Crystalline Hierarchical Architecturesmentioning
confidence: 99%
“…To avoid the above problems, a dynamic light‐activated photoalignment technique was adopted to control the 3D smectic layer curvature . Figure C‐I schematically shows a digital mirror device‐based photopatterning system, which can easily accomplish arbitrary planar anchoring patterns.…”
Section: Light‐activated Liquid Crystalline Hierarchical Architecturesmentioning
confidence: 99%
“…However, these methods are often complicated and limited to producing gratings with a fixed grating constant. Liquid crystal (LC), a typical soft building block, has the ability to self-assemble into various hierarchical superstructures [5][6][7]. Thanks to the high responsiveness to diverse external stimuli, LC gratings have played important roles in tunable optical components for light manipulation [8][9][10].…”
Section: Introductionmentioning
confidence: 99%